Borrowed concepts in closely related languages (MAIDAN) - Смирнова, Татьяна Николаевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article examines the transformation of the Ukrainian exoticism of the Maidan into a complete borrowing that has lost its connection with a certain event and the significance of the "mass opposition to resistance", as well as the conceptual features of this token, its value properties. The author of the article watched of the development of the concept in Russian media discourse. This concept has acquired new value meanings in the Russian conceptosphere, which distinguish it from the values of the donor language. The value component of the concept is determined by social factors and therefore has a different content in the Russian language of Russia and Ukraine. The ambivalence of the value semantics of the Maidan concept is a characteristic feature of the recipient language.